Semidiurnal Internal Tides Observed on the Eastern Flank of Hanna Shoal in the Northeastern Chukchi Sea. Issue 11 (10th November 2022) - Fang, Ying‐Chih; Janout, Markus; Kawaguchi, Yusuke; Statscewich, Hank
Abstract: This paper investigates the role of semidiurnal tides in the Hanna Shoal region on the northeastern Chukchi Sea shelf to evaluate their impact on the regional shelf dynamics. The study is based on 2‐year long velocity time series from five oceanographic moorings. These records indicate the dominance of wind‐generated near‐inertial energy during the summer season with low ice cover. However, when the ocean is fully covered by sea ice, tides dominate the variability in the semidiurnal energy band. The records reveal considerable seasonal variability as well as regional differences, where barotropic tides dominate in the well‐mixed waters west of Hanna Shoal while bottom‐trapped internal (depth‐dependent) tides are observed east of Hanna Shoal, where stratification can persist year‐round. Resulting tide‐driven shear in winter east of Hanna Shoal under stratified conditions can occasionally reach the level of a Richardson number below 1 and can be as low as ∼0.25, implying the likelihood of shear instability and potentially eroding lower water column stability. This may lead to upward fluxes of near‐bottom nutrient‐rich Winter Water and thus carries ecosystem implications. Our study indicates that the internal tides east of Hanna Shoal are modulated by the spring‐neap cycle and result from the interaction of barotropic tides with local bathymetry and stratification. Plain Language Summary: We investigated currents, temperature, and salinity records from five oceanographic moorings around Hanna Shoal in the northeast Chukchi Sea in the Arctic Ocean. The data indicate different water column structures and therefore different vertical structures of the tides between the east and west sides of Hanna Shoal. The water column on the west side is mainly homogeneous during winter, while the east side can remain stratified year‐round. The presence of stratification then leads to vertical differences in tidal currents, which are larger in the lower part of the water column. Overall, our results indicate that tides interact with stratification and bottom topography east of Hanna Shoal. The resultant vertical tidal velocity differences have a potential to promote water exchange in the water column, even underneath an ice‐covered ocean in winter and spring. This mechanism may supply important nutrients to the sunlit upper ocean in the spring and summer, and is thus potentially important for the Chukchi Sea ecosystem. Key Points: Tides dominate the semidiurnal variability of the Hanna Shoal region in winter during periods of high sea ice cover Semidiurnal internal tides exist in the eastern Hanna Shoal region, while the tides are largely barotropic in the west Semidiurnal internal tides induce current shear that, potentially, erodes lower‐layer stratification in winter